Increasing Maize Production in Palolo District, Sigi Regency: Challenges and Opportunities toward Food Independence - Muhammad Yasin; Hasmari Noer; Henny Indrawati (Postgraduate, University of Mataram, 2025)
Palolo district in Sigi regency has great potential in developing maize production as part of efforts to realize regional food self-sufficiency. However, increasing maize production in this area faces various challenges, including land limitations, climate change, and access to technology and markets. The study aims to determine the potential for increasing maize production based on the support of internal and external factors in Palolo district, Sigi regency. Sampling was done with a purposive sampling technique where members were selected intentionally, namely on the potential for increasing corn production in Palolo District, by tracing the population sampled by as many as 26 sample corn farmers. The data analysis used is SWOT analysis. The results of the research show that the potential for increasing maize production in Palolo district is supported by internal factors, among others: the existence of human resources in maize farming, the existence of superior seeds from the government, the increase in maize production, the existence of fertilizer subsidies, spray assistance from the government, and the direction of extension workers to farmers. External factors, such as the development of agricultural technology, the local government's support for maize farming, the increasing market demand for food, the availability of affordable facilities and infrastructure, and farmers' understanding of maize farming, also support this potential.